Enhancing Speaking Skills: Participatory Communication Strategies for Non-Language Lecturers - Saputri, Vike Aprilianin Marwintaria; Ajat, Ajat; Widiyanto, Widiyanto; Gautama, Sidartha Adi; Paramita, Santi; Wulan, Cening Ayu (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
In the era of globalization, effective communication skills have become increasingly crucial for educators, particularly those in non-language departments. This study investigates the impact of a Participatory Communication Approach on improving English speaking skills among lecturers from non-language departments at Jinarakkhita Buddhist College of Lampung. The research addresses the significant challenges faced by these lecturers, including linguistic difficulties, lack of confidence, and limited speaking practice opportunities. Employing a quantitative research design with a pretest-posttest experimental group approach, the study involved 20 lecturers (10 males, 11 females) from Buddhist Communication Science, Buddhist Education, and Buddhist Business and Management departments. The research was conducted from February 20th to April 20th, 2024, using Madsen's speaking skill rubric to assess participants' performance across five key dimensions: comprehension, pronunciation, grammar, vocabulary, and speech speed. The findings revealed a significant improvement in lecturers' speaking skills which is representing a 13.5% enhancement. The study concludes that this approach provides a supportive, collaborative learning environment that helps non-language lecturers overcome communication barriers. By promoting active engagement, peer feedback, and interactive learning, institutions can effectively develop lecturers' English-speaking skills, ultimately improving educational quality and global academic interactions.